1999
DOI: 10.1007/s002130050890
|View full text |Cite
|
Sign up to set email alerts
|

Task-dependent effects of the antidepressant/antipanic drug phenelzine on memory

Abstract: Phenelzine (PLZ) is a non-selective monoamine oxidase (MAO) inhibitor commonly used to treat depression and panic disorder. In addition to increasing levels of biogenic amines in the brain, PLZ elevates brain levels of the amino acid gamma-aminobutyric acid (GABA; Baker et al. 1991; present study). Given the extensive evidence implicating biogenic amines and GABA in mnemonic processes, PLZ may affect learning and memory. To investigate this possibility, male Sprague-Dawley rats were given PLZ sulfate (15 or 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…Zebrafish co-treated with L1 mimetic spent more time in the novel arm in comparison to the PQ-treated fish when their response to novelty was evaluated in the T-maze task, indicating an improvement of acquisition and consolidation of spatial memory. These findings are supported by the literature highlighting the improvement of learning and memory by PS and TC (Parent et al, 1999;Murakami et al, 2000;Yuede et al, 2007;Simpson et al, 2012). The improvement in the motor and non-motor deficits encouraged us to assess the neurochemical modifications upon co-treatment with PS or TC.…”
Section: Discussionsupporting
confidence: 76%
“…Zebrafish co-treated with L1 mimetic spent more time in the novel arm in comparison to the PQ-treated fish when their response to novelty was evaluated in the T-maze task, indicating an improvement of acquisition and consolidation of spatial memory. These findings are supported by the literature highlighting the improvement of learning and memory by PS and TC (Parent et al, 1999;Murakami et al, 2000;Yuede et al, 2007;Simpson et al, 2012). The improvement in the motor and non-motor deficits encouraged us to assess the neurochemical modifications upon co-treatment with PS or TC.…”
Section: Discussionsupporting
confidence: 76%
“…Chronic treatment with the tricyclic antidepressant amitriptyline, which inhibits 5HT and noradrenaline reuptake, enhances spatial learning in the water maze in young rats and prevents the age‐induced impairment observed in this task, possibly by reducing anxiety levels (Yau et al ., 1995, 2002). Conversely, however, the acute administration of the monoamine oxidase inhibitor phenelzine increases retention in an inhibitory avoidance task, but increases escape latencies and path lengths in the Morris water maze (Parent et al ., 1999). In clinical studies, tricyclic antidepressants have been shown to bring about deficits in working memory (Amado‐Boccara et al ., 1995; Caldeira de Carvalho et al ., 2002), while selective 5HT and noradrenaline reuptake inhibitors have little effect on memory (Siepmann et al ., 2001; Cassano et al ., 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of phenelzine is an elevation of brain levels of biogenic amines, including alanine and GABA [118][119][120]. In turn, glutamine levels are decreased [119], and, since alanine is an inhibitor of glutamine synthase [121], it may be postulated that its accumulation, conceivably due at least in part to AGXT inhibition, may induce a secondary reduction in brain glutamine levels [122].…”
Section: Alanine Aminotransferasementioning
confidence: 99%